Diet soft drink is associated with increased odds of proliferative diabetic retinopathy. (23rd February 2018) - Fenwick, Eva K; Gan, Alfred TL; Man, Ryan EK; Sabanayagam, Charumathi; Gupta, Preeti; Khoo, Krystal; Aravindhan, Amudha; Wong, Tien Y; Lamoureux, Ecosse L
Abstract: Importance: While consumption of soft drink may increase the risk of cardiovascular disease, the relationship between soft drink consumption and diabetes complications is unknown. Background: To explore the association between regular and diet soft drink consumption, and diabetic retinopathy (DR) and diabetic macular oedema (DME). Design: Clinical, cross‐sectional study. Participants: Adult patients with diabetes recruited from a tertiary eye hospital (Melbourne, Australia) answered a Food Frequency Questionnaire. Methods: None, moderate and high soft drink consumption was defined as <1, 1–4 and >4 cans/bottles (375 mL) per week, respectively. Due to missing data, data were imputed using the multiple imputation chained equation procedure. Multivariable logistic regression models determined the associations between soft drink consumption, and presence and severity of DR/DME. Main Outcome Measures: Presence and severity of DR/DME. Results: Of the 609 participants (mean age ± standard deviation: 64.6 ± 11.6 years; males = 210), 285 (46.8%) and 190 (31.2%) consumed diet and regular soft drink, respectively. A total of 230 (37.8%), 36 (5.9%), 154 (25.3%), 28 (4.6%) and 146 (24.0%) had no DR, mild non‐proliferative DR (NPDR), moderate NPDR, severe NPDR and proliferative DR (PDR), respectively. High diet soft drink consumption was independently associated with increased likelihood of having PDR (odds ratio = 2.51, 95% confidence interval = 1.05–5.98), compared to no consumption. In contrast, regular soft drink was not associated with DR or DME. Conclusions and Relevance: Consuming >4 cans (1.5 L)/week of diet soft drink is associated with a more than twofold risk of having PDR in patients with diabetes. Longitudinal studies are needed to further elucidate the association and its underpinning mechanisms.